Structural Characteristics and Anisotropic Carrier Mobility of Two-dimensional Carbon Nitride C12N2 - Liu, Jian (International Journal of Materials Science and Technology Studies, 2025)
Two-dimensional (2D) carbon nitrides are attracting growing interest because of their structural diversities and distinctive electronic properties. A first principles investigation has been carried out on a new 2D carbon nitride C12N2 with orthorhombic lattice. The carbon nitride C12N2 shows medium electronic band gap of 1.01 eV, high carrier mobility about of 2.2×105 cm2V-1s-1, suggesting that it is a promising candidate used on short channel transistors. The strain behavior of C12N2 has been studied, revealing that it can endure a uni-axial strain or compression of up to ±10%. Furthermore, the band edge positions, effective masses and band gap are seriously changed under different level of strains. It suggests that appropriate tensile strain can effectively overcome the short channel effect in semiconductor device.